2015
DOI: 10.1016/j.redox.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Redox signaling in acute pancreatitis

Abstract: Acute pancreatitis is an inflammatory process of the pancreatic gland that eventually may lead to a severe systemic inflammatory response. A key event in pancreatic damage is the intracellular activation of NF-κB and zymogens, involving also calcium, cathepsins, pH disorders, autophagy, and cell death, particularly necrosis. This review focuses on the new role of redox signaling in acute pancreatitis. Oxidative stress and redox status are involved in the onset of acute pancreatitis and also in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 221 publications
(278 reference statements)
2
76
0
7
Order By: Relevance
“…Acute pancreatitis is a localised inflammation of the pancreatic gland leads to local and systemic complications [33]. In this study, L-arg was used to induce experimental AP in rats, whereas its mechanism to induce pancreatitis is not fully clear.…”
Section: Discussionmentioning
confidence: 97%
“…Acute pancreatitis is a localised inflammation of the pancreatic gland leads to local and systemic complications [33]. In this study, L-arg was used to induce experimental AP in rats, whereas its mechanism to induce pancreatitis is not fully clear.…”
Section: Discussionmentioning
confidence: 97%
“…When studies on TNF-α are examined, it is observed that anti-TNF-α treatment is effective on pancreatic cell healing 19 . In addition, many conducted studies have shown that an increase in IL-1β and IL-6 levels may be precursor markers of pancreatic damage and these levels were seen to decrease after treatment 5 . In this study, EA was seen to correct increased IL-1β, IL-6, and TNF-α levels seen during AP in the AP-EA group, and these results were confirmed by histopathological evaluations as well.…”
Section: Figure 1 -Hematoxylin-eosin (Hande) Staining (X200) Microscopmentioning
confidence: 99%
“…The mean incidence around the world is 40/100 2,3 . Many studies have shown that cytokines such as IL-1β, IL-6, and TNF-α 4,5 , which are secreted due to ductal obstruction and ductal injury as well as oxidative stress, are involved in the pathogenesis of AP 6,8 . Oxidative stress, through reactive oxygen species, can damage the membrane resulting in lipid peroxidation, and alter the cytosol dynamics leading to early activation of pancreatic digestive enzymes that initiate pancreatic damage.…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen substances (ROS) may also contribute to the damage of pancreatic acinar cells. 4,[6][7][8][9][10] Previous studies have confirmed the participation of ROS at early stages of AP, regardless of the underlying cause. [11][12][13] The characteristics of the pancreatitis induced by cerulein (a decapeptide and cholecystokinin analogue) resemble the early phase of AP in humans.…”
mentioning
confidence: 99%